Penegakan Hukum terhadap Pelaku Tindak Pidana Penambangan Pasir Secara Illegal - Anastasia Esa Ananta (Savana, 2024)
Mining is a natural resource that cannot be renewed so it must be managed as well as possible, efficiently and transparently and paying attention to the environmental impacts resulting from mining activities. The rampant illegal sand mining that occurs in Batam, Indonesia can certainly cause environmental damage. The aim of this research is to determine and analyze the regulation and law enforcement against perpetrators of illegal sand mining crimes. The research method used in this research is descriptive-analytic with a juridical-normative type of research. The results of research on regulations regarding perpetrators of illegal sand mining crimes are regulated in Article 158 which reads "every person who carries out mining without a permit as intended in article 35 shall be punished with a maximum imprisonment of 5 (five) years and a maximum fine of IDR 100,000,000,000 .00 (one hundred billion rupiah)”. Law enforcement against perpetrators of criminal acts of illegal sand mining, namely being sentenced by the Batam District Court with Batam District Court Decision No. 515/Pid.Sus/2022/PN Btm is the sentence imposed by the panel of judges including imprisonment for 1 year and 3 months for each defendant, as well as a fine of IDR 500,000,000.00. The conclusion is that law enforcement is running well and shows the court's seriousness in dealing with violations of mining and environmental protection laws. Additional punishment in the form of imprisonment if the fine is not paid, emphasizes that compliance with the law is non-negotiable.